Empowering Santri to Create Sustainable Economy at Pondok Pesantren Munzalan Mubaroka Siliragung Banyuwangi through Asset-Based Community Development (ABCD) - Nurul Inayah; Lely Ana Ferawati Ekaningsih; M. Alaika Nasrulloh (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Eco-Islamic boarding schools or green Islamic boarding schools are efforts to provide a